PENGARUH RELIGIOSITAS DAN PENDAPATAN TERHADAP KEPUTUSAN PEMBELIAN MAKANAN HALAL - Fatimatuz Zahro, Jihan; Dwi Retno Widiyanti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The purpose of this study was to determine the effect of religiosity and income on purchasing decisions for halal food in Malang city. In this study the data used is primary data through questionnaires. The variables consist of religiosity (X1), income (X2) and halal food purchasing decisions (Y). The data were analyzed using the structural equation model (SEM). The results showed that religiosity has a significant influence on purchasing decisions. In addition, the income variable has a significant influence on purchasing decisions. In summary, it can be said that religiosity and income are important factors that influence individual purchasing decisions. The implication of this research is through improving skills and education related to halal food consumption in the form of educational campaigns and religious counseling programs regarding halal food. Agency cooperation with various parties such as religious leaders is needed to support the implementation of the halal center listed in the RPJMD of Malang City.